Digital Well-Being in Castilla y León, a New Opportunity for the Tourism Sector - García Nistal, Alejandro; Aznar, Tomás; Debasa, Felipe (Journal of Tourism, Sustainability and Well-being, 2022)
In recent years we are experiencing great changes worldwide that lead to rethinking and looking at things from other points of view. The search for digital well-being brings us closer to the adoption of healthy lifestyle habits using the technology that surrounds us. Because of this the Community of Castilla y León in Spain, rich in history, traditions and culture, finds technology useful to endorse its entire tourist tradition, as an example of the relationship between aspects of healthy living and the use of digital technology. These factors allow a sustainable tourism that is necessary at this time when resources are beginning to feel limited; something that have been seen very necessary throughout the COVID-19 pandemic. In this study, we discussed the changes provoke by COVID-19 pandemic using a geographical case study focused on Castilla y León. We discussed the results relative to digital well-being in tourism and its influence in local enterprises.